Heavy Metals Contamination of Soil in Urban Areas of Southern Ural Region of Russia - Kuramshina, Natalya; Rebezov, Maksim; Kuramshin, Ens; Krasnogorskaya, Natalya; Tretyak, Lyudmila; Somova, Yuliya; Dolmatova, Irina; Zaitseva, Tatiana; Grigoryeva, Irina; Bakirova, Lyaila; ., . (International Journal of Engineering and Technology, 2018)
We studied the influence of mining, refining and petrochemical enterprises to the soil contamination by heavy metal of the Southern Urals and adjacent territories. It is established that the highest values of soil contamination study area with heavy metals (pollution degree ZÑ = 17,4; 20,4) was observed in the zone of influence of the mining and processing plant. The area adjacent to the machine-building, oil refining and petrochemical industries in major cities of Bashkortostan, was characterized by valid (ZÑ = 1.9 to 5.5) or weak impurity (ZÑ = 8,1; 13,8). In the operation level is set to contamination of urban soils by heavy metals under the influence of the mining and metallurgical industries of the Southern Urals of emissions from machine-building enterprises, oil-refining and petrochemical companies, operating in large, medium and small cities of Bashkortostan.Â